Seasonal Variation on Physiochemical Parameters and Macrophytes Production of Rupa Lake, Kaski, Nepal - Kunwar, Devendra; Devkota, Anjana (Journal of Natural History Museum, 2015)
The Rupa lake is the third largest and heavily tampered lake of Pokhara Valley. Physiochemical parameters like, water temperature, pH, dissolved oxygen (DO), total nitrogen (TN) and PO4-P and biomass of aquatic macrophytes were analyzed during pre and post-monsoon. Biomass ranged from 27.25g/m2–389.25g/m2 throughout the experimental period and the highest biomass was observed during post-monsoon period. Regarding the growth form, the highest biomass was represented by emergents (251.16 ± 95.16g/m2) and lowest biomass by submerged species (48.39 ± 7.27g/m2). The lake can be categorized as eutrophic. J. Nat. Hist. Mus. Vol. 26, 2012: 80-87